2007
DOI: 10.1056/nejmoa072006
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment with Prednisolone or Acyclovir in Bell's Palsy

Abstract: In patients with Bell's palsy, early treatment with prednisolone significantly improves the chances of complete recovery at 3 and 9 months. There is no evidence of a benefit of acyclovir given alone or an additional benefit of acyclovir in combination with prednisolone. (Current Controlled Trials number, ISRCTN71548196 [controlled-trials.com].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
345
3
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(391 citation statements)
references
References 20 publications
9
345
3
17
Order By: Relevance
“…The role of antiviral medication remains controversial. 5 Despite the generally favorable prognosis of Bell palsy, many patients do not recover fully, particularly those with either complete flaccid paralysis or prolonged recovery periods.…”
Section: Discussionmentioning
confidence: 99%
“…The role of antiviral medication remains controversial. 5 Despite the generally favorable prognosis of Bell palsy, many patients do not recover fully, particularly those with either complete flaccid paralysis or prolonged recovery periods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed evidence for the presence of herpes simplex virus in some cases of bell's palsy [5,6], thus anti-viral agents were applied in some cases. Approximately 70% of all patients recover completely, and a higher percentage of improvement is achieved if corticosteroid therapy is prescribed [14,15]. Early physical rehabilitation is performed in severe grades of paresis [16].…”
Section: Discussionmentioning
confidence: 99%
“…10 In the past literature, randomized, double-blind, placebocontrolled trials have provided compelling evidence that treatment with prednisolone improves outcome in patients with Bell's palsy and shortens the time to complete recovery. 11 Extensive chemoradiation used in the transplantation procedure can be highly toxic because of the underlying DNA repair defect in FA. Histocompatible (matched) sibling donor transplant remains the best treatment for FA and gives the best outcome, if performed early.…”
Section: Discussionmentioning
confidence: 99%